Implementation of Problem Based Learning Model to Improve Student Learning Activities: Classroom Action Research at MIS Sumber Mas Ganding Sumenep - Rosyida, Vina Nur; Khasanah, Uswatun; Rahmawati, Wahidah; Fitrianingsih, Uun; Hasanah, Uswatun (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to enhance student learning activities through the implementation of the Problem-Based Learning (PBL) model and to explore its practical application in elementary school classrooms. The research was conducted as a Classroom Action Research (CAR) at MIS Sumber Mas Ganding, Sumenep, involving fifth-grade students and focusing on the sub-theme